The Bibliography of Ontario History/La Bibliographie d'histoire ontarienne, 1976-1986 - Lonardo, Michael (Labour / Le Travail, 1991)
The article reviews the book, "The Bibliography of Ontario History/La Bibliographie d'histoire ontarienne 1976-1986," by Gaétan Gervais, Gwenda Hallsworth and Ashley Thomson.
Keywords: BIBLIOGRAPHY of Ontario History (Book); BOOKS -- Reviews; GERVAIS, Gaetan, 1944-; HALLSWORTH, Gwenda; History; LA Bibliographie d'histoire ontarienne 1976-1986 (Book); Nonfiction; Ontario; THOMSON, Asley